7 - Private Returns on Education in Ghana: Estimating the Effects of Education on Employability in Ghana - Prince Asafu-Adjaye, (African Sociological Review, 2013)
The relevance of education for both individual and social development in Ghana and in many developing societies is generally acknowledged. Human capital theorists identify positive effects of education on labour market outcomes of individuals. It has been argued that education enhances the skills and knowledge of individuals for better employment, higher productivity and improved wages. This paper draws on the latest and most comprehensive survey data in Ghana, the fifth round of the Ghana Living Standards Survey (GLSS 5), to assess the effects of education on employability in Ghana. This paper argues that education has a positive effect on employability in Ghana. Analysis of the GLSS 5 data shows that in the Ghanaian labour market, individuals who have attained basic, secondary and tertiary education have higher probabilities of being employed than those with no education, ceteris paribus. However, the highest private returns on education, in terms of employability is tertiary education. Hence optimal post primary education investment in Ghana is one with a high possibility for tertiary education.